Nanopositioning and - measuring technique - Jäger, Gerd; Manske, Eberhard; Hausotte, Tino; Büchner, Hans-Joachim; Grünwald, Rainer (Proceedings Volume 4900, 7th International Symposium on Laser Metrology Applied to Science, Industry, and Everyday Life, 2002)
At the Institute of Process Measurement and Sensor Technology of the TU Ilmenau, a scanning force microscope (measuring range 15 mum x 75 mum x 15 mum) having a laser-interferometric 3D-nanomeasuring system free from Abbe errors has been developed in cooperation with the PTB Braunschweig. The extended measuring uncertainty (K = 2) is only 0.2 nm and was obtained with a structure standard. To achieve a considerable extension of the measuring range up to 25 mm x 25 mm x 5 mm, a nanopositioning and -measuring machine was developed. The resolution of the measuring axes is 1.24 nm. The laser-interferometric measurement is free from Abbe errors of 1(st) order in all measuring axes. The deviations of the guides used are compensated by means of a precision mirror corner.
Keywords: Miniature laser interferometer; optical fiber; x-y-stage with plane mirror interferometer; vibrometer; measuring atomic force microscope; nano-measuring machine